Integrating Educational Technology: Policies and Practices for Inclusive Learning - Onuh Matthew Ijiga; Olanrewaju Awoyemi; Fadeke Adeola Atobatele; Chioma Angela Okonkwo (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The integration of educational technology has the potential to revolutionize teaching and learning by enhancing accessibility and inclusivity. This paper reviews current policies, best practices, and future directions in the field of educational technology with a focus on fostering inclusive learning environments. It begins with an overview of the significance of educational technology and the importance of inclusivity, followed by an examination of existing policies and their impact on inclusive education. The paper then explores successful case studies and examples of effective technology integration, highlighting tools and platforms that promote inclusivity and the necessity of teacher training and professional development. Addressing the challenges faced in integrating technology, the paper outlines strategies to overcome barriers such as the digital divide, insufficient training, and resistance to change. Future directions include emerging trends such as artificial intelligence, virtual and augmented reality, and blockchain technology, with policy recommendations to enhance technology access and inclusivity. The vision for the future emphasizes the creation of adaptive and accessible educational environments that cater to diverse learning needs and support equitable learning opportunities for all students.